Static memory materials - Sexty, Dénes; Wetterich, Christof (Arxiv, 2018)
We simulate static memory materials on a two-dimensional lattice. The bulk properties of such materials depend on boundary conditions. Considerable information can be stored in various local patterns. We observe local probabilities oscillating with the distance from the boundary. The dependence of the local statistical information on this distance can be described by a linear evolution of classical wave functions, including the superposition principle and classical interference. We speculate that these new phenomena could open new algorithmic possibilities analogous to quantum computing.